2009
DOI: 10.1111/j.1365-2478.2009.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Gravity contributions to the understanding of salt tectonics from the Jebel Cheid area (dome zone, Northern Tunisia)

Abstract: A B S T R A C TDetailed gravity measurements integrated with geological data were computed to constrain the mechanisms that were active during the emplacement of the Triassic evaporite-bearing folds of Jebel Cheid from the salt-dome zone in the Atlassic region. The gravity analysis consists in mapping the contrasting gravity responses: complete Bouguer anomaly, residual anomaly and derivative maps; the main results display a positive amplitude gravity anomaly as the response of Triassic evaporite bodies and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…7) Jebel Cheid, Jebel Mourra et Lansarine (Benassi et al, 2006;Hamdi Nasr et al, 2009;Amiri et al, 2011;Sarsar Naouali et al, 2017). Ces réponses indiquent la présence des roches denses comme l'anhydrite et la dolomie en subsurface.…”
Section: Carte De L'anomalie Résiduelleunclassified
“…7) Jebel Cheid, Jebel Mourra et Lansarine (Benassi et al, 2006;Hamdi Nasr et al, 2009;Amiri et al, 2011;Sarsar Naouali et al, 2017). Ces réponses indiquent la présence des roches denses comme l'anhydrite et la dolomie en subsurface.…”
Section: Carte De L'anomalie Résiduelleunclassified
“…The area of study belongs to the ''diapirc zone'' of Northern Tunisia, which is characterized by numerous Triassic outcrops generally elongated with a NE bearing; they bear gypsum, clay, some metasomatized basalts (sills, dikes), sands as well as lime-and dolostones. Due to its heterogeneous mixture, Triassic material would be denser (HAMDI NASR et al, 2007;HAMDI NASR et al, 2009), leading to the observed positive gravity response (HAMDI NASR et al, 2009;BENASSI et al, 2006).…”
Section: Bandpass Filteringmentioning
confidence: 99%
“…In the region, an Early Mesozoic rifting phase has structured basin sunk salt dominated Triassic deposits, and was seconded by a passive margin tectonic basin style during the entire meso-cenozoic times. Moreover, Northern Tunisia has been the subject of several gravity data analysis (JALLOULI et al, 2002;JALLOULI et al, 2005;INOUBLI and MANSOURI, 2006;BENASSI et al, 2006;ROBINSON et al, 2007;HAMDI NASR et al, 2008;HAMDI NASR et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we used gravity data in the northern Tunisian Atlas collected by the Office National des Mines (ONM) [46] (gravimetric map of Teborsouk area). The studied area is covered by gravity stations on a 1 × 1 km 2 grid.…”
Section: Gravity Datamentioning
confidence: 99%
“…The Neogene formation is composed of Miocene marls. The Pliocene-Quatenary series shows a conglomeratic beds on the base and of sandy clay ones on the top [35,[41][42][43][44][45][46].…”
Section: Geological Settingmentioning
confidence: 99%